PENGARUH MODERASI GREEN BANKING DALAM HUBUNGAN ANTARA CORPORATE SOCIAL RESPONSIBILITY DAN GOING CONCERN - Devi Malinton; Kunradus Kampo (Dinamika Akuntansi Keuangan dan Perbankan, 2019)
This study investigates the effect of corporate social responsibility on going concern, and the effect of green banking as moderate on relationship between corporate social responsibility and going concern. Population used in this study is the whole bank listed on Indonesia Stock Exchange (IDX) period 2013 – 2016. Total samples are 11 banks for 4 years selected by purposive sampling method and using secondary data, i.e. annual report, financial report, and sustainability report collected from IDX database and each bank’s official website. Analysis results show that the effect of corporate social responsibility in bank can increase going concern. The findings also indicate that green banking is able to moderate the relationship between corporate social responsibility and going concern, but green banking has weak influence as a moderating variable. These findings imply going concern is measured by not only financial aspect but also the impact that company gives to its social environment. Keywords: corporate social responsibility, going concern, and green banking.